Mewujudkan Good Governance Dalam Rangka Meningkatkan Kualitas Pelayanan Publik - Fahrinda Khansa Pramesti; Sapto Budoyo (PGRI Kota Semarang, 2026)
The implementation of democratic, good, and wise government administration is a top priority in efforts to support the progress of national civilization in the era of globalization. In reality, public services are still marred by various problems such as complicated procedures and low responsiveness that impact public trust. This study aims to analyze the implementation of good governance to improve the quality of public services and identify obstacles and their implementation. The application of good governance principles including professionalism, accountability, and transparency, Government Regulation Number 101 of 2000 and UNDP standards are strategic instruments of bureaucratic reform. Success rests on synergy: the government as regulator, the private sector as actors, and the public as service users. This effort still faces obstacles such as limited quality of human resources, discipline from service providers, and suboptimal public participation. The conclusion is that the implementation of good governance in public services involves several roles in order to create good public services. Standardization of quality services and orientation to community needs are absolute requirements for realizing national welfare.